Treatment of brewery wastewater using electro-Fenton and granulated activated carbon. Issue 1 (1st January 2018) - Ogbiye, Adebanji S.; Omole, David O.; Ade-Balogun, Kehinde D.; Onakunle, Olumuyiwa; Elemile, Olugbenga O.
Abstract: Improvement of electro-Fenton (EF) process with granulated activated carbon (GAC) for the treatment of brewery effluent obtained from Ota, South-West Nigeria was investigated. The GAC was obtained by crushing, carbonising, sieving, and activating cow bones. Duplicate samples of the raw effluent and 10 treated brewery effluent samples were analysed for conductivity, turbidity, total dissolved solids (TDS), chemical oxygen demand (COD), copper, manganese, cadmium, lead, and zinc. The average readings were taken as final values. Results showed that the combined use of EF and GAC treatment of the effluent yielded better result than use of EF alone. The removal efficiency was 1181, 50, 565, 4375, 160, and 840% for turbidity, COD, copper, cadmium, lead, and zinc respectively. EF and GAC treatment were, however, found to be inefficient for the treatment of conductivity, TDS, and manganese. It was also found that pH had a direct impact on the treatment media. Turbidity and cadmium, which had the highest removal rates were achieved at pH 2, while COD, copper, and zinc had optimum treatment at pH 6. It was concluded that the combined advantage of electrolytic separation from EF and adsorption from GAC yielded better treatment result for the brewery effluent samples.